Pengaruh Gaya Hidup Hedonis terhadap Perilaku Konsumtif di Kalangan Mahasiswa - Mira Nurazijah; Syaipia Laila Nur Fitriani; Tin Rustini (Departement of Mathematics Education, 2023)
Being a society amid the development of information and technology, has an impact on life with all the conveniences. However, because of this ease, it is no doubt that people have the desire to continue to follow the trends that are happening and lead to a hedonic style or an attitude that is concerned with self-satisfaction. In fulfilling this style, it will lead to consumptive behavior as a style that likes to spend money without thinking about its usefulness. This research was conducted to find out how the level of hedonic style causes consumptive behavior. The method used is mixed method, which is a combination of quantitative and qualitative approaches. The research data came from each student which was conducted on November 6-10 2022. Respondents who were none other than students admitted that they were individuals who always wanted to get what they wanted. But in this study, the consumptive behavior of the influence of the hedonic style of students on what they always want is still moderate.